Penentuan Tarif Ideal Pengiriman Barang Berdasarkan Perhitungan Biaya Operasional Kendaraan - Syafrianita,; Gibran Dhiyaulhaq,; Hartati M Pakpahan,; Lukman Abdul A Hakim, (ReTII, 2023)
The decision to set tariffs is an important choice that helps the company's operations run well. This study aims to determine the ideal tariff for shipping goods based on the calculation of vehicle operating costs and to determine when the break-even point occurs based on the ideal tariff. Companies engaged in goods delivery services compete to provide excellent service and competitive prices. PT Dapensi Dwikarya is one of the vehicle rental service companies for the transportation of goods and people. Delivery of goods on the Cirebon-Indramayu route is the route with the most transportation in the Bandung area operations. The results of the study in the minimum charge condition with a 10% fee obtained a tariff of Rp.143/Kg for a minimum load capacity of 2,000 Kg. The net profit that will be obtained is Rp. 95,537 / unit / rite. The accuracy of the selling price or service provided is influenced by the accuracy of tariff determination.